Policy Analysis of the HKPD Law: Strengthening PAD from Motor Vehicle Tax in Probolinggo City and Regency - I Nyoman Teja Kusuma; Ika Devy pramudiana; Nihayatus Sholichah (International Journal of Social Science and Humanity, 2026)
The enactment of Law Number 1 of 2022 concerning Financial Relations between the Central and Regional Governments (HKPD Law) introduced a pivotal shift in Indonesia’s fiscal decentralization through the Motor Vehicle Tax (PKB) "opsen" (option) mechanism. This study analyzes the impact of HKPD Law implementation on local revenue (PAD) strengthening in Probolinggo City and Regency. Utilizing a qualitative comparative case study approach, the research evaluates administrative readiness and policy impacts derived from Ministry of Finance Regulation (PMK) Number 3 of 2024. The findings reveal an asymmetrical transition, where fiscal effectiveness is highly contingent on digital infrastructure maturity and geographical constraints. Probolinggo City demonstrates successful host-to-host system integration, ensuring daily liquidity and bureaucratic efficiency. Conversely, Probolinggo Regency faces "geospatial gaps," characterized by transaction data delays and high collection costs in remote areas. This study identifies a lack of target alignment between provincial and local governments and emphasizes the necessity of "budget tagging" for road infrastructure to enhance the social contract with taxpayers. This research contributes to fiscal decentralization theory by proposing a "geographic coefficient" model for operational cost distribution in developing regions.